Kurikulum STEM (Science, Technology, Engineering, Mathematics): Mempersiapkan Siswa untuk Masa Depan yang Berorientasi Teknologi - Ikhbar Fathoni; Adi Gunawan; , Gusmaneli (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The STEM (Science, Technology, Engineering, and Mathematics) curriculum plays a crucial role in preparing students to face challenges in the digital and globalized era. This study aims to analyze the importance of the STEM curriculum in modern education, as well as the challenges faced in its implementation in Indonesia. Using a literature review method, this research identifies various factors affecting the effectiveness of the STEM curriculum, including teacher training, educational infrastructure, and policy support. The findings indicate that while the STEM curriculum can enhance students' interest in science and technology, challenges in its application still need to be addressed. Therefore, collaboration between the government, schools, and communities is essential to optimize the implementation of the STEM curriculum, enabling students to develop relevant skills for an increasingly complex future.